Promosi Kesehatan dengan Video Efektif Meningkatkan Pengetahuan dan Sikap Ibu Hamil Trimester III dalam Pemilihan Metode Kontrasepsi Pasca Persalinan - Ni Putu Manik Primarani; Ni Wayan Manik Parwati; Ni Putu Riza Kurnia Indriana; Idah Ayu Wulandari (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2023)
Video is a type of audiovisual media that is effectively used for mass learning processes, individuals and groups. Video expected to help pregnant women, especially in the third trimester, in selecting the contraceptive method. To determine the effectiveness of health promotion through video toward knowledge and attitude of the third trimester pregnant women in the selection methods of post labor contraception. This study employed pre-experimental design with one group pretest-posttest design. The research was conducted at Public Health Center I of Public Health Office, East Denpasar from September 12th to October 14th 2022. There were 35 respondents recruited as sample of the study which recruited through non probability sampling in the form of convenience sampling. The data were collected by using questionnaire. The data were analyzed by using Wilcoxon Rank Test. The finding showed that the knowledge level obtained the p-value = 0.001 and the attitudes obtained the value of p = 0.001. Because the value of p <0.05, Ha was accepted, meaning that health promotion with videos was effective in increasing the knowledge and attitudes of third trimester pregnant women in selecting postpartum contraceptive methods at Public Health Center I of Public Health Office, East Denpasar. Suggestions are addressed to health workers, midwives and further researchers. Keywords: Postpartum blues, Knowledge, Attitude